THE RESULTS OF THE STUDY OF THE CHARACTERISTICS OF SOCIAL LONELINESS IN ADOLESCENTS IN URBAN AND RURAL AREAS (World Bulletin of Public Health, 2023)
Social loneliness is a state when a person thinks that he or she has been abandoned, excluded, pushed away, not appreciated. He sees himself as an extra person, a loner, an outsider. In our society nowadays there is a dynamic growth in the number of adolescents who are in a state of social loneliness, leading to depression, conflict, preventing the establishment of trusting relationships, forming a negative type of self-perception and leading to a sense of psychological breakdown, mental disorder
Keywords: loneliness; adolescents; rural areas